Directional multi‐band antenna employing frequency selective surfaces. Issue 4 (1st February 2013) - So, H.; Ando, A.; Seki, T.; Kawashima, M.; Sugiyama, T.
Abstract : Proposed is a concept of a directional multi‐band antenna employing frequency selective surfaces (FSSs). To confirm the feasibility of the concept, the proposal is implemented by combining a metal reflector, two FSSs that act as frequency filters, and a multi‐band radiator. The proposed triple‐band antenna can radiate at 800 MHz (the metal reflector or FSS 1), 2 GHz (FSS 2), and 4 GHz (FSS 3). FSS 2 passes waves at one frequency band (800 MHz) and reflects all other bands, and FSS 3 passes waves at two frequency bands (800 MHz/2 GHz) and reflects all other bands. Beam control is easy since all that is needed is to change FSS size and/or the distance between the radiator and metal reflector/FSS. Electromagnetic field simulations and measurements demonstrate good directivity in the frequency bands of 800 MHz, 2 GHz and 4 GHz.